Hospitalization rates for intussusception in children aged 0-59 months from 2009 to 2014 in Italy - Vincenzo Restivo; Claudio Costantino; Fabio Tramuto; Francesco Vitale (Taylor & Francis Group, 2017)
The real cause of intussusception is not fully understood and a variety of conditions have been associated with it (Meckel diverticulum, polyps, duplication cysts, parasites, Henoch-Schönlein purpura, cystic fibrosis, hemolytic-uremic syndrome and infectious gastroenteritis). Furthermore few European countries, following WHO recommendation to monitor baseline incidence of intussusception before implementation of immunization program for rotavirus, used intussusception rate as a baseline value to compare the same figures in the period before and after introduction of vaccination. In this study, data of intussusception hospitalizations occurred among Italian children aged 0 through 59 months from 2009 to 2014 were analyzed. A total amount of 3,088 children were included, accounting for a hospitalization rate of 20.2 per 100,000. Overall, the hospitalization rate for intussusception had a slight increase in trend from 2009 to 2014 (18%). In particular children 0-11 months had a hospitalization rate higher than 12-59 months with an aggregate value of 36 Vs. 16 per 100,000 respectively. Among all children hospitalized for intussusception a total of 239 (7.7%) had also a previous or concomitant hospitalization for gastroenteritis. This study demonstrates that Italian hospitalizations for intussusception are increasing by time and the role played by different risk factors, including acute gastroenteritis, have to be investigated in the future. These data could be useful to monitor intussusception hospitalization in the perspective of anti-rotavirus vaccination introduction in Italy.